Peran Penting HAKI (HAK KEKAYAAN INTELEKTUAL): Hak Paten di Era Globalisasi - hikam, Ichsanul Hikam; Romi Faslah (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This paper discusses the importance of protecting Intellectual Property Rights (IPR), especially patent rights, in facing challenges and opportunities in the era of globalization. Patents provide exclusive rights to inventors over their inventions, thus encouraging innovation, protecting copyright, and increasing the competitiveness of national industry. In the context of modern business and economy, patents play a strategic role as high-value commercial assets. The discussion in this paper includes the definition of patent rights, their role in encouraging economic growth and innovation, and legal protection provided through various laws and regulations in Indonesia, such as Law Number 13 of 2016 concerning Patents. This paper also highlights the obstacles in the implementation of patent rights, such as low public awareness, complicated bureaucratic processes, and weak law enforcement, as shown through a study of the e-KTP patent defense case. With a strong and effective patent protection system, Indonesia is expected to create an innovative and globally competitive business environment.